The Impact of Science Capital on Self-Concept in Science: A Study of University Students in New Zealand - Turnbull, Steven Martin; Meissel, Kane; Locke, Kirsten; O'Neale, Dion R. J. (Frontiers in Education, 2020)
Understanding factors that contribute to students' self-concept in science is an important task in boosting the number of students studying science and retaining students in science fields. A questionnaire was administered to science students at the University of Auckland in New Zealand (N = 693) to test a theoretical model of science self-concept tied to the work of Pierre Bourdieu. In this model, a student's social capital (i.e., relationships with parents, teachers and peers) and cultural capital (i.e., science related resources) are seen as key determinants of a student's belief that science is a domain in which they can succeed. Results from a Structural Equation Model (SEM) show that, of the factors included in the model, exposure to passionate science teachers during high school was the main predictor of science self-concept for our sample of university science students, while having peers who value science was also found to be important. Interestingly, science-related resources and parents' value of science were not significant predictors of science self-concept, but the number of university generations in the family did have a positive association. Students who self-identified as male had higher levels of science self-concept, even after accounting for social and cultural factors in our theoretical model. Implications of these findings are discussed in the context of the field of science education and Bourdieu's sociological theory.